1994
DOI: 10.1177/107110079401501204
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodesis of the Ankle with Lateral Plating

Abstract: A modification of internal fixation compression arthrodesis for ankle fusion is described using two 6.5-mm cancellous bone screws and a lateral T plate. Using this technique, 20 consecutive arthrodeses by one surgeon were reviewed. Solid union was attained in 19 of 20 patients (95%). Average follow-up was 18 months (range 6-59 months). Time to obtain solid arthrodeses averaged 18 weeks. In 11 patients who returned for follow-up, clinical grading using the Mazur scale score averaged 70 of 90 points. Diagnoses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 13 publications
0
24
0
3
Order By: Relevance
“…In both the anteroposterior and lateral views, the centre of the talar dome should line up with the centre of the tibial axis [23,[25][26][27]. Arthrodesis is achieved with two to five large fragment (6.5-7.3 mm) cancellous screws, or plates [8,24,28,29].…”
Section: Techniquesmentioning
confidence: 99%
“…In both the anteroposterior and lateral views, the centre of the talar dome should line up with the centre of the tibial axis [23,[25][26][27]. Arthrodesis is achieved with two to five large fragment (6.5-7.3 mm) cancellous screws, or plates [8,24,28,29].…”
Section: Techniquesmentioning
confidence: 99%
“…A recent biomechanical study has shown superior stability of an ankle fusion using internal fixation with a plate and screws versus fixation with screws alone (14) . Several authors have reported successful use of internal fixation with plates and screws utilizing various techniques including lateral plating, anterior dual plating and custom blade plate techniques (15)(16)(17)(18)(19) . Three additional studies report using anterior tension plate techniques for tibiotalar arthrodesis after failed total ankle arthroplasty (20)(21)(22) .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Rowan and Davey also reported a high fusion rate (94%) and few complications with the use of anterior AO T-plates in 33 patients. 12 Gruen and Mears used a posterior blade plate for late reconstruction of five ankles with complex deformity.…”
Section: Discussionmentioning
confidence: 96%